2019
DOI: 10.1590/s1677-5538.ibju.2018.0530
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in skeletal muscle index one year after radical cystectomy as a prognostic indicator in patients with urothelial bladder cancer

Abstract: Purpose The present study aimed to determine whether sarcopenia after radical cystectomy (RC) could predict overall survival (OS) in patients with urothelial bladder cancer (UBC).Materials and Methods The lumbar skeletal muscle index (SMI) of 80 patients was measured before and 1 year after RC. The prognostic significance of sarcopenia and SMI decrease after RC were evaluated using Kaplan–Meier analysis and a multivariable Cox regression model.Results Of 80 patients, 26 (32.5%) experienced sarcopenia before RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Ultimately, our meta-analysis comprised 21 studies, as depicted in Figure 1. 2040 Specific details of the included studies are presented in Table 1. The majority of studies (n = 19) had a retrospective design, while two studies had a prospective design.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, our meta-analysis comprised 21 studies, as depicted in Figure 1. 2040 Specific details of the included studies are presented in Table 1. The majority of studies (n = 19) had a retrospective design, while two studies had a prospective design.…”
Section: Resultsmentioning
confidence: 99%
“…The change in SMI is not considered. Ha et al showed a significant change in sarcopenia and SMI 1 year after radical cystectomy and might be an effective marker for oncological outcome ( 31 ). Another limitation of this study is the time of follow-up after RP, which limits the statement of sarcopenia effecting BCR.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 126 records were identified from databases and 27 duplicated records were removed. Eventually, nine studies were included [19][20][21][22][23][24][25][26][27]. The detailed selection process was shown in the Fig 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…Among nine retrospective included studies, 1476 patients were enrolled and the sample size ranged from 80 to 500 [19][20][21][22][23][24][25][26][27]. Among four of included studies the cutoff values of SMI, 55cm 2 /m 2 for male and 39cm 2 /m 2 for female, were applied [19,21,24,27].…”
Section: Basic Characteristics Of Included Studiesmentioning
confidence: 99%